The rise of the global imaginary political ideologies from the French Revolution to the global war on terror - Steger, Manfred B. 1961- (Oxford University Press, 2009)
Combining political history, philosophical interpretation and story-telling, Steger traces ideology's remarkable journey from de Tracy's Enlightenment 'science of ideas' to George W. Bush's 'imperial globalism'. He finds in '-isms' an ability to articulate deep-seated understandings of community in global rather than national terms.